The definition, classification, and prognosis of chronic kidney disease: a KDIGO Controversies Conference report - Levey, Andrew S.; de Jong, Paul E.; Coresh, Josef; El Nahas, Meguid; Astor, Brad C.; Matsushita, Kunihiro; Gansevoort, Ron T.; Kasiske, Bertram L.; Eckardt, Kai-Uwe (Kidney international, 2011)
The definition and classification for chronic kidney disease was proposed by the National Kidney Foundation Kidney Disease Outcomes Quality Initiative (NKF-KDOQI) in 2002 and endorsed by the Kidney Disease: Improving Global Outcomes (KDIGO) in 2004. This framework promoted increased attention to chronic kidney disease in clinical practice, research and public health, but has also generated debate. It was the position of KDIGO and KDOQI that the definition and classification should reflect patient prognosis and that an analysis of outcomes would answer key questions underlying the debate. KDIGO initiated a collaborative meta-analysis and sponsored a Controversies Conference in October 2009 to examine the relationship of estimated glomerular filtration rate (GFR) and albuminuria to mortality and kidney outcomes. On the basis of analyses in 45 cohorts that included 1,555,332 participants from general, high-risk, and kidney disease populations, conference attendees agreed to retain the current definition for chronic kidney disease of a GFR <60ml/min per 1.73m2 or a urinary albumin-to-creatinine ratio >30mg/g, and to modify the classification by adding albuminuria stage, subdivision of stage 3, and emphasizing clinical diagnosis. Prognosis could then be assigned based on the clinical diagnosis, stage, and other key factors relevant to specific outcomes. KDIGO has now convened a workgroup to develop a global clinical practice guideline for the definition, classification, and prognosis of chronic kidney disease.